PENGARUH BANK SYARIAH TERHADAP PERTUMBUHAN EKONOMI PROVINSI JAWA BARAT - Saeranti Sri Pramoda Wardani; Purnama Putra (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
This study examines the influence of Islamic banks on the economic growth of West Java Province by comparing the number of Assets, Financing, and Third Party Funds in Islamic Banks in West Java Province with the Gross Regional Domestic Product (GRDP) of West Java. As well as this research proves whether Islamic banks affect economic growth in West Java with several research variables, namely total assets, financing, and deposits on operating income and gross regional domestic product (GRDP). The data in this research is secondary time series data obtained from Islamic banking statistical data, which is published regularly on the official website of Bank Indonesia, and West Java GRDP Growth Data which is published regularly on the official website of the West Java Central Bureau of Statistics. Multiple regression is the appropriate analytical tool to measure the contribution of the banking sector to the economy of West Java. The results of this study note that the t value of the asset variable is 3.251 greater than the t table of 1.99167 with a sig value of 0.002 <0.05, so it is concluded that assets have a significant effect on the GRDP of West Java Province, and the calculated t value of the financing variable is 3.350 greater than t table 1.99167 with a sig value of 0.001 <0.05 so that it can be concluded that the financing variable has a significant effect on the PDRB of West Java Province, and the calculated t value of the DPK variable is 2.776 greater than t table 1.99167 with a sig value of 0.007 <0.05 so it can be concluded that the DPK variable has a significant effect on the GRDP of West Java Province.